Metabolic syndrome among diabetic patients : A study between primary care clinic and diabetic specialist clinic in Kuantan, Pahang - Abdullah, Fa’iza; Tin, Myo Han; Md Aris, Mohd Aznan; Osman, Iskandar Firzada (2016)
Central obesity, diabetes, hypertension and high cholesterol make up a cluster of metabolic syndrome (MetS) which is one of the most dangerous cardiovascular disease (CVD) risk factors that definitely increases the burden on national healthcare systems. Ø However, there is limited data on the prevalence and sociodemographic profile of Type-2 Diabetes Mellitus (T2DM) patients with metabolic syndrome.